Systematic literature review of entrepreneurship mentoring in higher education: a comparative study of Malaysia, China, the USA, and the UK - Noraini Hashim; Hariyaty Ab Wahid (Penerbit Universiti Kebangsaan Malaysia, 2024)
This paper presents the key findings of a Systematic Literature Review (SLR) aimed at investigating the mentoring approaches practiced by Higher Education Institutions (HEIs) in Malaysia, China, the United States of America (USA), and the United Kingdom (UK) to enhance their support systems for aspiring post-graduation entrepreneurs. Recognizing the growing significance of entrepreneurship in today's society, these HEIs have emphasized entrepreneurial mentorship to support and nurture student entrepreneurs. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology, the review focuses on two primary objectives. Firstly, it aims to identify the competencies required by mentor entrepreneurs who are lecturers within these institutions. Secondly, it seeks to identify the specific areas of emphasis in mentoring entrepreneurs within HEIs in the four selected countries. The selected articles are categorized into three main themes: entrepreneur mentoring competencies, entrepreneurship mentoring focus, and the mentoring approaches practiced at HEIs in these countries. The findings reveal that mentor entrepreneurs, typically lecturers, possess essential competencies, including personality traits, practical experience, relevant skills, and comprehensive knowledge of entrepreneurship. Differences and similarities in the focus and approach to mentoring entrepreneurs are observed among the four countries, reflecting their unique entrepreneurial landscapes and cultural contexts. However, commonalities also exist, particularly in the overarching goal of supporting and nurturing aspiring entrepreneurs. In conclusion, this SLR highlights the competencies required by mentor entrepreneurs and sheds light on the diverse approaches adopted by HEIs in Malaysia, China, the USA, and the UK to mentor and guide students in entrepreneurship. These findings can inform the development of effective mentoring programs tailored to the specific needs and challenges faced by aspiring entrepreneurs in different educational contexts.